2010
DOI: 10.1021/jf9040723
|View full text |Cite
|
Sign up to set email alerts
|

Isoliquiritigenin Entails Blockade of TGF-β1-SMAD Signaling for Retarding High Glucose-Induced Mesangial Matrix Accumulation

Abstract: Diabetic nephropathy characterized as mesangial fibrosis and glomerulosclerosis results in renal failure and end-stage renal diseases. Enhanced expression and secretion of connective tissue growth factor (CTGF) play an important role in the expansion of glomerular mesangial matrix mostly composed of type IV collagen. Isoliquiritigenin can prevent various renal injuries via its anti-inflammatory action. However, the effect of isoliquiritigenin on diabetic nephropathy has never been explored. The present study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 30 publications
2
30
0
Order By: Relevance
“…Many studies have fully confirmed that high glucose is a positive regulator of TGF-b1 expression in various cells such as human mesangial cells (Li et al 2010), mouse embryonic stem cells ) and rat renal proximal tubular cells . LY294002 or shAkt vector both attenuated high glucose-induced enhanced TGF-b1 and FN expression in HKC cells, which revealed the involvement of PI3K/Akt in extracellular matrix accumulation of HKC cells and also determined that high glucosecaused TGF-b1 up-regulation and extracellular matrix protein production could be suppressed by blocking PI3K/Akt activation pathway.…”
Section: Discussionmentioning
confidence: 96%
“…Many studies have fully confirmed that high glucose is a positive regulator of TGF-b1 expression in various cells such as human mesangial cells (Li et al 2010), mouse embryonic stem cells ) and rat renal proximal tubular cells . LY294002 or shAkt vector both attenuated high glucose-induced enhanced TGF-b1 and FN expression in HKC cells, which revealed the involvement of PI3K/Akt in extracellular matrix accumulation of HKC cells and also determined that high glucosecaused TGF-b1 up-regulation and extracellular matrix protein production could be suppressed by blocking PI3K/Akt activation pathway.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, the regulation of TGF-β1/Smad signaling plays a critical role in the development of DN. Agents [14][15][16] targeting enhancement of Smad7 protein expression and then suppression of TGF-β1 signaling transduction may reverse the functional and pathological changes of DN.…”
Section: Discussionmentioning
confidence: 99%
“…They found that it reversed the marked increases in collagen secretion and CTGF expression caused by HG. It also boosted HG-plummeted type matrix metalloproteinase-1 (MT-1 MMP) expression and dampened HG-elevated tissue inhibitor of MMP-2 (TIMP-2) expression, facilitating the degradation of mesangial matrix and diminished mesangial matrix accumulation in response to ambient HG through retarding TGF-beta1-SMAD signaling transduction 29 .…”
Section: Isoliquiritigeninmentioning
confidence: 99%